PANCASILA SEBAGAI IDEOLOGI - Supriyatno, Arie (Universitas Muhammadiyah Magelang, 2010)
Pancasila as an ideology is open to have essentially a fixed value, but penjabarannya can be developed creatively and dynamically according to the needs of dynamic development of Indonesian society. Constitutional accountability is plainly saying that the Constitution, as the written form of the Basic Law that instituted the atmosphere mysticism behind it, just set the basic rules. MPR as the embodiment of all the people of Indonesia to observe the dynamics of the community, and outline the direction that will be used as guidance in realizing the ideals of the nation.Pancasila is not a dogma, nor a religion, and will never diagamakan. The statement could be interpreted as a rationale for the plan to develop the instrumental values of Pancasila consistently, both in the economic, social, cultural, political, and defense security.